2018
DOI: 10.2147/jmdh.s175195
|View full text |Cite
|
Sign up to set email alerts
|

Using information and communication technology in the recovery after a coronary artery bypass graft surgery: patients’ attitudes

Abstract: BackgroundPatients who have undergone a coronary artery bypass graft (CABG) surgery are exposed to physical and mental problems after discharge from the specialist hospital and are often in need of post-discharge support and follow-up.AimThis study aimed to explore the attitudes of CABG patients toward using information and communication technology (ICT) during the first year of recovery after discharge from hospital.MethodsA cross-sectional design utilizing an electronic survey was employed. The sample consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…This phase focused on conceptual construction of the website, in particular its setting, capacity and usability in fulfilling patient needs. Data collected from the analysis phase was used to design learning content according to patient needs which was then supported through findings obtained from literature review [12][13][14][15]. MyEducation:CABG application comprises of six components: Heart; Coronary Artery Disease; CABG Surgery; Recovery Planning Support (i.e.…”
Section: Design Phasementioning
confidence: 99%
See 1 more Smart Citation
“…This phase focused on conceptual construction of the website, in particular its setting, capacity and usability in fulfilling patient needs. Data collected from the analysis phase was used to design learning content according to patient needs which was then supported through findings obtained from literature review [12][13][14][15]. MyEducation:CABG application comprises of six components: Heart; Coronary Artery Disease; CABG Surgery; Recovery Planning Support (i.e.…”
Section: Design Phasementioning
confidence: 99%
“…But the use of now-indispensable Information and Communication Technology (ICT) could facilitate manual to virtual conversion of said information. Approximately 70% of patients undergoing cardiac surgery accessed the internet for information shortly upon being informed of the procedure, hence making the internet a powerful educational platform [12,13]. Cognitive behavioral technique based internet programs developed to guide patients through virtual contact with a healthcare professional have emerged a particularly effective option.…”
Section: Introductionmentioning
confidence: 99%
“…Of total searches entered into a search engine, 4.5% are health‐related 1 . Many patients who undergo coronary artery bypass graft (CABG) surgery report difficulty in comprehending information retrieved from the internet regarding this procedure, and some find the information not to be useful 2,3 . Additionally, the internet is used by the majority of patients seeking to information about medical conditions 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Many patients who undergo coronary artery bypass graft (CABG) surgery report difficulty in comprehending information retrieved from the internet regarding this procedure, and some find the information not to be useful. 2,3 Additionally, the internet is used by the majority of patients seeking to information about medical conditions. 4,5 YouTube is the most popular video website in the world, now with more than one billion global users.…”
mentioning
confidence: 99%
“…Approximately 70% of patients consult the internet for information soon after learning about their upcoming surgery [ 21 , 22 ]. Studies [ 23 , 24 ] have reported that eHealth interventions for cardiac rehabilitation can also improve patients’ quality of life.…”
Section: Introductionmentioning
confidence: 99%